Unusual “Mini-Rugby Ball” Pattern Solitary Lung Metastasis in Relapsed Ewing's Sarcoma - Gondhane, Abhay; Sonavane, Sunita N.; Basu, Sandip (World Journal of Nuclear Medicine, 2024)
Ewing's sarcoma (ES) is a mesenchymal origin malignant neoplasm that affects children and adolescents. It is the second most common type of bone sarcoma and accounts for approximately 1.5% of all childhood cancers with an annual incidence of 1 to 3 cases per million children under 16 years of age. In this article, we present the case of a 16-year-old adolescent girl. Lung metastasis at the initial diagnosis of ES is relatively uncommon but carries significant prognostic implications. Lung metastases in ES can vary significantly in size, ranging from small nodules (just a few millimeters in size) to the largest reported case being 15 cm. The size of the metastases impacts the choice of therapeutic strategies and the prognosis. Approximately 30% of patients with ES experience a relapse, with the lungs being a common site for metastatic disease. Relapsed lung metastasis on follow-up is a critical concern in the long-term management of ES. We describe a relapsed case of ES in a 16-year-old adolescent girl who presented with a solitary large metastatic right lung mass, with the longest dimension of 16 cm on craniocaudal measurement. The primary site of the tumor was the left distal femur, for which the patient received six cycles of neoadjuvant chemotherapy, followed by en bloc tumor excision and rotationplasty of the left distal femur, after which the patient received seven cycles of adjuvant chemotherapy. Subsequent 5 years of regular follow-up was asymptomatic. Later, the patient presented with back pain and cough, and was diagnosed with a solitary large right lung mass. Computed tomography (CT) guided biopsy of the right lung mass revealed a metastatic ES, for which she underwent chemoradiotherapy. This case highlights the large size of solitary lung metastases in relapsed ES.
Keywords: Ewing's sarcoma; 18F-NaF; 18F-FDG; PET/CT; lung metastases